1995
DOI: 10.1287/mnsc.41.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Strategic Investment Decisions Under Sequential Technological Change

Abstract: Strategic decisions to invest in new equipment are critical not only because of the large initial capital costs incurred but even more importantly because they affect future unit production costs, revenues, and the ability of the firm to perform operations that were not possible earlier. Thus these decisions determine the very competitiveness of the firm. Further, decisions regarding the choice of technology are very expensive to correct if incorrect decisions are identified. These decisions have become increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…Thus, the values of these strategies are the same as the value of the strategy "never invest" and therefore they can be ignored for the moment. An equivalent application of this so-called forecast horizon procedure can be found in Nair (1995).…”
Section: Single Switchmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the values of these strategies are the same as the value of the strategy "never invest" and therefore they can be ignored for the moment. An equivalent application of this so-called forecast horizon procedure can be found in Nair (1995).…”
Section: Single Switchmentioning
confidence: 99%
“…Of course, this threshold is the option value of waiting. Nair (1995) uses a dynamic programming framework to solve the technology adoption problem for a firm. First the model is solved for a finite planning horizon before which a fixed number of new technologies will arrive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their model assumed that the costs associated with the present and future technologies are known, but the appearance times of the future technologies are uncertain. Nair [19] also studied uncertain sequential technological change, which affects the firm's strategic investment decisions. He suggested that the appearance of the future technologies are considered uncertain with probabilities that may vary with time, but the order in which they appear is assumed sequential, such as the different generations of microchips for personal computers.…”
Section: Relevant Capacity Expansion Studiesmentioning
confidence: 99%